A taxa de desemprego em segunda geração de modelos de crises cambiais: uma aplicação para o caso brasileiro - Nazaré, Ronaldo (2008)
This dissertation formalizes a theoretical model, illustrating Brazilian s Central Bank preferences, introducing unemployment rate in the analysis. The aim is to check the behaviour of the monetary authority towards traditional macroeconomic variables and unemployment rate, during the 1994 - 1999 period. This work is firstly motivated by Eichengreen and Jeanne (2001). For a better adaptation to the Brazilian context, the model here presented proposes a fusion of the above authors and Ferreira and Tulio (2001). Both have characteristics of second generation models of exchange rate crises. The study follows this order: i. Historical review of the period of the observation; ii. The model here proposed and the reasons for fusion; iii. Brief review of the characteristics of generations of models of exchange rate crises; iv. Econometric test; and, v. Conclusion. The research has found that, during the first five years of Real Plan, a period characterized by three exchange rate crises, unemployment rate performace has had revealed little importance to the Brazilian Central Bank.